Islamic Financial Literacy Level in Jayapura - Abidin, Muhamad Zainal; Affandy, Fachrudin Fiqri; Pratiwi, Ira Eka; Karman, Abd. (LAA MAISYIR : Jurnal Ekonomi Islam, 2022)
Complete and credible information is of course very much needed by the community. This will affect people's attitudes in making decisions about financial institutions. This study aims to determine the level of financial literacy of the people of Jayapura City, Papua Province. The object of this research is the people of Jayapura City and the subject of research is public knowledge of Islamic financial institutions, financial management, and public confidence in managing finances. The data used in this study is primary data through a questionnaire. A sample of 230 respondents. Data processing with SPSS with a percentage descriptive analysis approach. The results showed that the level of Islamic financial literacy in the Jayapura city community was still low, namely only 41%. This is due to the lack of education about finance to the public, as well as the lack of public interest in using sharia products. The underlying factors are due to gender, income level, education, and occupation. This research is expected to be the basis of reference for policy making by policy makers in the city of Jayapura.